Avaliação de indicadores de planejamento e controle da produção na construção : boas práticas, eficácia e prazo - Oliveira, Carla Barroso de (2010)
The effective implementation of appropriate development plans to the reality of the work becomes a crucial issue for a good construction companies performance. The ability to presage potential barriers in implementation enterprise enables companies to work in uncertain environments and solve any problems prior to the execution tasks, thereby protecting the production. The emergence of a new concept for management construction has been widely discussed, the Lean Construction. Given a set of practices linked to concepts and basic principles of Lean Construction and considered essential for effective planning, evaluation was made in 33 plans prepared by a consulting planning firm. Thus it was possible to achieve the main goal of this research: assessing the impact of good practices of PCP in the planning construction effectiveness. Other objectives were: evaluate the impact of effective planning and control in enterprise performance, analyze the causes for the non-completion of work packages, verify variations in indicators of production performance according to the type of company, and check for correlation between indicators studied. The results hasn t shown a direct relationship between the indicators. It was observed that 65% of good planning practices were used by the consulting planning firm and that it, along with its contractors, may improve the effectiveness of the planning process. It was possible to determine a valid model for predicting the time deviousness.